Time Will Fly During Future Fun (But Drag Until Then). Issue 3 (26th May 2021) - Tonietto, Gabriela N.; VanEpps, Eric M.; Malkoc, Selin A.; Maglio, Sam J.
Abstract : Consumers' lives are filled with scheduled events—both positive and negative. The current research examines how the valence of future scheduled events colors consumers' temporal judgments in relation to such events: the time until their onset, the time during the events, and the time until their offset. We propose that the lay theory espousing "time flies when you're having fun" leads consumers to judge that positive (vs. negative) future events of equivalent objective distance and duration are farther away and shorter . Operating in tandem, these elements produce two novel phenomena: (a) The end of positive and negative events can feel similarly far from the present, and (b) The beginning and end of positive events can feel similarly far from the present, whereby, in some circumstances, the event's duration is effectively eliminated in the mind's eye. Four studies provide evidence for these predictions, informing future directions regarding prospective time perception.